2005
DOI: 10.1016/j.jacc.2004.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on myocardial perfusion after primary angioplasty in patients with acute myocardial infarction

Abstract: Despite similar high rates of TIMI flow grade 3 after primary PCI in patients with and without diabetes, patients with diabetes are more likely to have abnormal myocardial perfusion as assessed by both incomplete STR and reduced MBG. Diminished microvascular perfusion in diabetics after primary PCI may contribute to adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 34 publications
2
57
2
3
Order By: Relevance
“…25 Despite similar high rates of TIMI flow grade 3 after primary PCI in patients with and without diabetes, DM was an independent predictor of absent myocardial perfusion (MPG 0/1) (hazard ratio …”
Section: Primary Pci In Diabetic Patientsmentioning
confidence: 96%
See 1 more Smart Citation
“…25 Despite similar high rates of TIMI flow grade 3 after primary PCI in patients with and without diabetes, DM was an independent predictor of absent myocardial perfusion (MPG 0/1) (hazard ratio …”
Section: Primary Pci In Diabetic Patientsmentioning
confidence: 96%
“…31,32 These deleterious consequences of abnormal glucose metabolism on microvascular perfusion have been well documented using new modalities to quantify myocardial reperfusion in patients treated with primary stent PCI. 25,33 The no-reflow phenomenon, which corresponds to a closed muscle, was found more often in patients with hyperglycaemia than in those without hyperglycaemia and the blood glucose level on admission was found to be an independent prognostic factor for no reflow (figure 5). Whether decreased microvascular perfusion accounts for the higher rate of mortality has been a subject of debate.…”
Section: Why Do Reperfusion Therapies Fail In Diabetics With Stemi?mentioning
confidence: 99%
“…No-refl ow phenomenon is found in 25% to 30% patients with AMI, despite successful coronary reperfusion and is associated with a worse outcome (17,18). Studies have demonstrated that acute hyperglycemia is associated with reduced spontaneous coronary perfusion and impaired tissue perfusion as compared to euglycemia (19,20). In a study of Iwakaru et al (6), patients with AMI and no-refl ow phenomenon were found to have higher blood glucose levels on admission than did those without no-refl ow phenomenon despite the similar frequency of DM and similar levels of hemoglobin A1C values of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, no data were reported on myocardial perfusion. In fact, diabetes has been shown to be associated with impaired reperfusion (16).…”
Section: L I N I C a L C A R E / E D U C A T I O N / N U T R I T I mentioning
confidence: 99%